1990
DOI: 10.1038/nbt0790-651
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Production in Baculovirus-Infected Insect Cells

Abstract: We have employed the baculovirus expression system for the production of a mouse monoclonal IgG antibody directed against lipoprotein I of Pseudomonas aeruginosa. Both light and heavy chain cDNAs were introduced into the baculovirus genome in a single step of homologous recombination. Insect cells that were infected with the recombinant virus stably secreted antigen-binding and glycosylated antibody molecules capable of binding the complement component C1q.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 26 publications
0
26
1
Order By: Relevance
“…The ratios of complex, hybrid, and paucimannosidic glycoforms in the secreted IgG are not unlike those obtained at the Asn 25 site of interferon-␥ secreted from Ea-4 cells (22). In addition, the current results indicate the presence of difucosylated N-glycans.…”
Section: Comparison Of Hplc Oligosaccharide Profiles In the Presence contrasting
confidence: 62%
“…The ratios of complex, hybrid, and paucimannosidic glycoforms in the secreted IgG are not unlike those obtained at the Asn 25 site of interferon-␥ secreted from Ea-4 cells (22). In addition, the current results indicate the presence of difucosylated N-glycans.…”
Section: Comparison Of Hplc Oligosaccharide Profiles In the Presence contrasting
confidence: 62%
“…To overcome these problems other expression systems such as mammalian (Dorai et al, 1994;Jost et al, 1994), insect (Putlitz et al, 1990), yeast (Bowdish et al, 1991;Davis et al, 1991), plant (Firek et al, 1993), and in vitro translation systems (Nicholls et al, 1993) have been used to produce rAb fragments (compared in (Verma et al, 1998)). The main advantage of yeast is that it is eukaryotic, has well understood genetics, and can be manipulated and cultivated easily and inexpensively.…”
Section: Introductionmentioning
confidence: 99%
“…Only little work has been done to characterize the glycosylation pattern of recombinant antibodies produced in insect cells. 3 Recently, two studies 62,82 have reported the presence of paucimannosidic and oligomannosidic glycans including α1,6 fucose without terminal sialic acids. Interestingly, when antibodies are expressed in insects, the higher Ig production rate observed in infected pupa is associated with a better processing of glycans, with five-fold GlcNacMan 3 GlcNac 2 structures found on N-glycans, suggesting that glycosylation may promote the expression of a new epitope involved in the secretion process.…”
Section: Enhancing the Production And Secretion Of Recombinant Antibomentioning
confidence: 99%
“…Different approaches have been tested to identify the best strategy for this purpose: (1) double infection with two separate heavy and light chain-expressing viruses, each gene being expressed under the control of the same viral promoter (PH or P10 promoter) and (2) the construction of a double-recombinant virus with both chains expressed independently under the same promoter. 2,3 Both approaches can present problems. Indeed one of the fundamental characteristics of these viruses, which has led to their use as expression vectors, is that they can induce a very efficient homologous recombination during their replication, thus facilitating the generation of recombinant viruses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation